Benchmarking sobre manufactura esbelta (lean manufacturing) en el sector de la confección en la ciudad de Medellín, Colombia - Arrieta Posada, Juan Gregorio (2010)
This document shows the results of a benchmarking study among different firms from the clothing industry that seeks to evaluate their degree of implementation in Lean Manufacturing during their respective productive processes. The study mainly targets firms that produce blue jeans, cotton shirts and t-shirts. Indeed, this industrial sector in the city of Medellin is highly developed and one of the most dynamic, thus the interest to perform an evaluation in this area. To achieve the benchmarking, a questionnaire was designed and applied to the different firms that were visited. The most significant result obtained was that Lean Manufacturing techniques were not prevalent within the general public. Only those companies with years in the business, exporters or foreign trademarks licensees, were knowledgeable of their application and development.